ANALISIS PENILAIAN KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN KARO - Naibaho, Dameria; Simbolon, Bernadetta Anita Jerry; Simanjuntak, Darmawati (Jurnal Budgeting, 2025)
This study aims to analyze the financial performance of the Karo Regency Government by using the Regional Financial Independence Ratio, Effectiveness Ratio of Regional Original Income, Regional Financial Efficiency Ratio, Harmony Ratio. This research method is a descriptive, qualitative method, with a population of the Karo Regency local government in 2019-2020. The data needed is the 2016-2020 Karo Regency Government Financial Report which was collected using documentation techniques. The test results show that the Financial Performance of the Karo Regency Government is quite good, we can see from the Independence Ratio, Effectiveness Ratio, Efficiency Ratio, and Harmony Ratio